Information Content of Insider Trades before and after the Sarbanes-Oxley Act - Brochet, Francois (The Accounting Review, 2010)
ABSTRACT: This study examines the information content of Form 4 filings under the more timely disclosure regime introduced by Section 403 of the Sarbanes-Oxley Act of 2002 (SOX). Abnormal returns and trading volumes around filings of insider stock purchases are significantly greater after SOX than before. Abnormal trading volumes around filings of insider sales are also greater post-SOX, on average, but stock returns are not more negative. However, once controlling for pre-planned transactions, reporting lag, litigation risk, and news following insider trades, I find a negative association between returns around filings of insider sales and SOX. Overall, the evidence suggests that the prompt public disclosures about insider transactions mandated by the new rule are relevant to the pricing of securities. The results are also consistent with SOX and regulatory actions reducing the incentives to sell ahead of privately known negative news.